“Wait, I can’t do that anymore!”: pandemic teacher immediacy in college communication classes - Chatham-Carpenter, April; Malone, Michelle (Frontiers in Education, 2023)
In this study, the researchers interviewed 15 communication instructors, using indepth semi-structured zoom interviews, about their experiences in the pandemic classroom and how they attempted to build relationships and connections with students during the COVID-19 pandemic. The researchers found specific immediacy strategies used by instructors, with participants indicating they attempted to use the more traditional teacher nonverbal immediacy behaviors such as eye contact, facial expressions, physical distance, and touch, but were hampered by the wearing of masks, practicing social distancing, and moving to online teaching modalities where student engagement was limited at best. Instructors also adapted verbal immediacy behaviors, as they used various strategies for inviting participation, providing feedback, and being real to develop connections with students, as well as building in specific teaching structures into their pandemic classrooms. In addition, participants indicated they used a variety of additional immediacy-related strategies and behaviors to build relationships once moving to blended HyFlex or online teaching. These strategies were used consistently, as instructors seamlessly moved between the online synchronous classroom, the blended classroom, and the face-to-face classroom with masking and physical distancing required. Our research revealed that there were unique ways relationships were built, typically using different types of media to enact teacher immediacy in nuanced ways. We argue that looking at such teaching using both media multiplexity and embodied pedagogy perspectives can enhance the teacher immediacy literature by demonstrating how teacher immediacy was changed during the pandemic, as media richness increased the likelihood of developing relationships between teachers and students through an embodied pedagogy of caring using technological tools.